Thermic Characteristics Of Rice Husk And Polyurethane Composite Materias As Insulation In Fish Cold Storage - Irwansyah; Balkhaya; Nuzuli Fitriadi; Herdi Susanto (Jurnal Inotera, 2021)
The process of freezing fish always requires a cooler as a temporary storage place for fish. The ability of the storage to maintain cold temperatures is a serious problem to be considered so that the freshness of the fish can be maintained. Therefore, an appropriate technology is required to support the cold chain system so that fish quality can be maintained. The purpose of this study was to test the thermal conductivity of composite materials for fish storage insulation from a mixture of rice husks and polyurethane so that the price of the box can be reduced but still maintain the quality of the fish. The composition of the composite material was made with a volume ratio of 1:0.5, 1:1, 1:1.5, and 1:2. The thermal conductivity test of the material uses the ASTM E1225-99 standard. All test results were compared with 100% polyurethane material. The results of testing the thermal conductivity of 100% polyurethane material obtained 0.023 W/m.C. From all the test results, the material that is most likely to be applied to fish cooler box insulation is a 1:1 composition having a thermal conductivity value of 0.067W/m.C. Materials with this composition do not affect the expansion of the polyol and isocyanate reactions. This composition is the most economical to be used as insulation for fish storage boxes which can save the use of polyurethane by 50%.